ANALYSIS OF SURFACE CONCENTRATION OF BLACK CARBON IN RIAU PROVINCE DURING THE 2019 FOREST FIRES USING MERRA-2 REANALYSIS DATA - Wilin Julian Sari; Dita Fatria Andarini; Fildzah 'Adany; Waluyo Eko Cahyono (Jurnal Meteorologi dan Geofisika, 2022)
Indonesia experienced forest fires almost every year, especially in the area of Riau Province, where as a result, pollutants such carbon dioxide and black carbon present in the air over Riau. Due to its size and its light absorption ability, black carbon is known to have bad impacts on the climate. This study aims to analyse the effect of forest fires that happened in Riau   province, Indonesia in September 2019 towards the production of black carbon, as well as to estimate backward air movement trajectory in order to confirm the air mass sources of the black carbon. The data of black carbon concentration used in this study is an hourly temporal data of MERRA-2 with a spatial resolution of 0.5° × 0.625°, while the trajectory calculation uses the HYSPLIT trajectory model. Linear regression of this study has an r value of 0.78 which shows that there is a positive correlation between black carbon concentration and number of hotspots. The range of BC concentrations were 2–11 × 10-9 kg.m-3 with higher concentration occurred during 9–23 September 2019 where it was affected by the south-easterly wind from Jambi and South Sumatera.